Internal Communication Challenges and Their Solution When Hybrid Work is Implemented in a Public Sector Organization: The Case Study of the Ministry of Transport and Communications of the Republic of Lithuania - Beniušis, Vytautas (Information & Media, 2023)
Effective internal communication (IC) increases employee productivity, loyalty to the workplace, strengthens organization’s reputation. Due to the pandemic, remote and later hybrid work became popular, though it caused challenges – how to use new technologies, motivate employees and control them as well as how to communicate with team members in new reality. The challenges of IC and its solution in the public sector, which has its own specifics, in the new hybrid work era have been studied fragmentarily. The study seeks to investigate the peculiarities of IC management in a public sector organization—the Ministry of Communications of the Republic of Lithuania—during the period of ongoing uncertainty. The methods of observation as well as semi-structured interviews with IC specialists and heads of the units were chosen for data collection. The results revealed that during the pandemic, prompt solutions, creation of personal connection and team motivation became particularly relevant for organizations. It was important for team leaders to find ways to replace the usual forms of communication to those applicable to the virtual space. New communication channels, such as top management meetings with employees online, helped to solve the problems of IC and to adapt to the new reality.